Additional Screw Added to the Femoral Neck System Could Enhance the Stability of Pauwel Type III Femoral Neck Fractures: a Finite Element Analysis - Cha, Yonghan; Park, Sunghoon; Jung, Chang Ho; Kim, Jin Woo; Yoo, Jun Il; Kim, Jung Taek; Jeon, Yongho; Han, Kyeong Jin (CiOS Clinics in Orthopedic Surgery, 2025)
Background: This study explores effective fixation methods for Pauwel type III femoral neck fractures by evaluating the biomechanical benefits of adding a screw to the Femoral Neck System (FNS). Methods: Computed tomography (CT) scans of an 82-year-old female patient with an intertrochanteric fracture were used to establish a finite element femur model with heterogeneous material properties. Finite element models of Pauwel type III fractures were created with and without an additional screw. The central and inferior trajectories of the FNS bolt were examined separately and combined with an additional screw for virtual fixation. Walking and stair-climbing loads were applied. Results: With the addition of a screw, both peak maximum and minimum principal strains consistently stayed comparable or decreased in models with both central and inferior bolt trajectories, while the volume of elements with principal strain exceeding 1% decreased by more than half. The peak von Mises stress observed in the implants ranged from 215.7 to 359.3 MPa, remaining below the titanium alloy's yield strength of 800 MPa. For normal walking, the addition of a screw to the central bolt trajectory model decreased the fracture gap by 50.6% and reduced sliding distance by 8.6%. For the inferior bolt trajectory, the gap was reduced by 57.9% and sliding distance by 25.0%. Under stair-climbing conditions, these improvements were also evident; the central trajectory model saw a halved fracture gap and a 7.9% decrease in sliding distance, while the inferior trajectory model experienced a 55.7% gap reduction and a 27.2% decrease in sliding distance. The additional screw increased the area ratio of the fracture site experiencing interfragmentary compression 34%–39%, while the additional screw alleviated peak interfragmentary compression by 12%–18% under both normal walking and stair-climbing conditions. Conclusions: The addition of a screw reduced the fracture gap, sliding distance, and peak interfragmentary compression, while increasing the area ratio of interfragmentary compression under both walking and stair-climbing loads, regardless of the FNS bolt trajectory, suggesting a better mechanical environment for fracture healing.
Keywords: Aged, 80 and over; Biomechanical Phenomena; Bone Screws; Female; Femoral Neck Fractures; Finite Element Analysis; Fracture Fixation, Internal; Humans; Tomography, X-Ray Computed; Biomechanical phenomena; Femoral neck fractures; Finite element analysis; Fracture fixation; Orthopedic fixation devices